THE MANUFACTURE OF LACTIC ACID BACTERIA GROWTH CURVE IN THE ISOLATION OF KEMBUNG (Rastrelliger sp) PEDA - Annisa Sharah; Rahman Karnila; Desmelati ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
This research aims to study and obtain a growth curve of lactic acid bacteria (LAB)which were isolate from kembung (Rastrelliger sp.) peda. The research method useddescriptive that was to do data analysis and presented in the form of bacterial growth curve.The analysis parameters were density, pH and total plate count (TPC). Isolate 15 was anisolate that have the biggest clear zone observed on the selection using GYP + CaCO3medium. The parameters used to determine the growth curve of BAL was Optical Densitytest, pH, Total Plate Count (TPC). Isolate 15 had 4 phases of growth. Adaptation phaseoccured at the time of 0-3 hours, logarithmic phase was a phase that was appropriate phase totook a culture of BAL as a starter occurred at a time 3 to 4 hours with a 0.867 A OD values,the number of cells 1,9x109 cfu / ml, and the pH value 5 , 1. Stationary phase occured in 4-5hours. Death phase occurred during the 5-8 hours it was intend for continuous decrease inthe number of bacterial cells with the smallest value that is 0,9x106 cfu/ml.Keywords: growth curve, Lactic Acid Bacteria, Kembung (Rastrelliger sp.) peda